AUDIT KEPUASAN KERJA BERDASARKAN KEBUTUHAN KARYAWAN - Anisa Putri; Isti Pujihastuti; Husnul Khatimah (JRAK: Journal of Accounting Research and Computerized Accounting, 2011)
The effective human resources management must fulfill the purpose of the company and the need of the employee. Work satisfactory is the effect of performance effectiveness and success of work. This research only discusses about work satisfactory audit based on the effectiveness of employee’s need in Universitas Islam “45” Bekasi. Employee’s satisfactory can be measured by satisfactory survey, often called attitude survey. Mc. Clelland mentioned that there are three kinds of employee’s need, first is need for achievement, = n Ach, second is need for affiliation, = n Af, and third is need for power, = n Pow. This research uses paradigm of quantitative research with descriptive-associative method which emphasizes the examination of theories through the measurement of research of variables with number by analyzing the data with statistic procedure. The researches with deductive approach to examine hypothesis. The variable of work satisfactory in Unisma is not maximal yet because the value in average has just reached 3.84 (the maximum score is 5), so that it can be asserted in percentage that the satisfactory of the employee has been reached around 76.8%. The indicator of work safety reaches the highest score (4.40), while the indicator of salary and benefit reaches the lowest score (2.69). In variable of employee’s need, the average value of employee’s need reaches 3.86, so that it can be asserted in percentage that the effectiveness of employee’s need has been reached about 77.2%. The highest score 4.3 is in the indicator of physical factor and work condition and the lowest score is in the indicator of emotion and work situation (3.09). The need for achievement reaches the highest score among Mc. Clelland’s three needs, which is 4.02, whereas the need for power and the need for affiliation each reaches 3.78 and 3.77. The variable of employee’s need, either need for achievement, need for power, or need for affiliation, can indicate the variety ofaudit variable of work satisfactory.